Transparansi Pengelolaan Dana Desa di Kabupaten Bireun - Ayumiati Ayumiati; Isnaliana Isnaliana; Jalilah Jalilah (Jurnal EMT KITA, 2019)
Village funds represent funds sourced from the State Revenue and Expenditure Budget which is intended for villages that are transferred through the Regency / City Regional Revenue and Expenditure Budget and are used to fund governance, development implementation, community development, and community empowerment, and transparency. The purpose of this study is to find out the transparency of village fund management in Bireun District. This type of research is descriptive analysis with a qualitative approach. The results showed that the management of village funds in Bireun district was transparent as evidenced by the openness in the process of planning, drafting and implementing the Village Fund Budget.